Investigation of disorder and its effect on electrical transport in electrochemically doped polymer devices by current–voltage and impedance spectroscopy. (1st February 2017) - Khan, Motiur Rahman; Anjaneyulu, P; Koteswara Rao, K S R; Menon, R
Abstract: We report on the analysis of temperature-dependent current–voltage characteristics and impedance measurements of electrochemically doped poly(3-methylthiophene) devices at different doping levels. The extent of doping is carefully tailored such that only the bulk-limited transport mechanism prevails. A transition from exponentially distributed trap-limited transport to trap-free space-charge-limited current is observed in current–voltage conduction upon increasing the doping. The obtained trap densities (3.2 × 10 16 cm −3 and 8.6 × 10 15 cm −3 ) and trap energies (31.7 meV and 16.6 meV) for different devices signify the variation in disorder with doping, which is later supported by impedance measurements. Impedance–frequency data for various devices can not be explained using the parallel resistance–capacitance ( RC ) model in the equivalent circuit. However, this was established by incorporating a constant phase element Q (CPE) instead of the capacitance parameter. It should be emphasized that low doping devices in particular are best simulated with two CPE elements, while the data related to other devices are fitted well with a single CPE element. It is also observed from evaluated circuit parameters that the spatial inhomogeneity and disorder are the cause of variability in different samples, which has an excellent correlation with the temperature-dependent current–voltage characteristics.